Pengaruh Pertumbuhan Penjualan, Likuiditas Dan Leverage Terhadap Profitabilitas (Studi Kasus Pada Perusahaan Tekstil dan Garmen yang Terdaftar di Bursa Efek Indonesia Periode 2015-2019) - Irni Yusnita (CV. ITTC INDONESIA, 2023)
This study aims to determine the effect of sales growth, liquidity, and leverage on the profitability of textile and garment companies listed on the Indonesian stock exchange for the period 2015-2019. This research is a quantitative research. The population of this study are all textile and garmen companies listed on the Indonesian stock exchange for the period 2015-2019. This sample selection was carried out by purposive sampling method and resulted in a selected sample of 35 sample. The data collection technique used was documentation, analysis techinique use descriptive analysis, classic assumption test and hypothesis test using multiple linear regression analysis with the tools of SPSS 16. The results showed that sales growth had no effect on profitability with a significant level of 0,153 > 0,05. Liquidity had no effect on profitability with a significant level of 0,352 > 0,05. And leverage had effect on profitability with a significant level of 0,013 < 0,05. Sales growth, liquidity, and leverage simultaneously influence profitability with a significant level 0,009 < 0,05. For the cofficient of determination or Adjusted R Square of 0,243or 24,3% wich mean that profitability can be sales growth, likuidity, and leverage by 24,3% while the remaining 75,7% is a variant not explained in this study.